Microcontroller-based sensory modules for cognitive therapy in multisensory rooms / Mohamad Amirul Mohamad Basri - Mohamad Basri, Mohamad Amirul (2018)
Multisensory room (MSR) is therapy prescription for stimulating senses in stages involving patient and therapist interaction. Therapy sessions are known to take effect at different rate depending on patient's condition and response, often across a long period of for it to be noticeable. Based on this reason, there is a need to improve connectivity and data collection that will allow clinical data analytic. This project presented a multisensory room design that offers added sensory input interfacing, connectivity for data storage and configuration for data analytics. The main objective is to develop effective data collection during multisensory therapy session. Second objective is to provide connectivity for multisensory room activities and patients experience data storage for clinical data analytics to take place. Third is to demonstrate data analytics using the data collected from the multisensory room. Under this framework, the therapy would be divided to five sub-modules. The first is when the patient meet the doctor or therapist assessment, to be given the clinical prescription. Second is therapist assessment, followed by the MSR session, then the post-MSR therapist assessment. The treatment is concluded by data analytics. MSR performed analysis to assist doctor's review of the prescribed MSR using artificial data that is incorporated into behavioural checklist and patient data. Visual representation and linear regression predictive model performed using SAS Viya and Visual Analytics. Index Terms-Analytical Data, Cognitive impairment Patient, Doctor, and Multisensory room